Fish facing global change: are early stages the lifeline?. (May 2019) - Vagner, Marie; Zambonino-Infante, José-Luis; Mazurais, David
Abstract: The role of phenotypic plasticity in the acclimation and adaptive potential of an organism to global change is not currently accounted for in prediction models. The high plasticity of marine fishes is mainly attributed to their early stages, during which morphological, structural and behavioural functions are particularly sensitive to environmental constraints. This developmental plasticity can determine later physiological performances and fitness, and may further affect population dynamics and ecosystem functioning. This review asks the essential question of what role early stages play in the ability of fish to later cope with the effects of global change, considering three key environmental factors (temperature, hypoxia and acidification). After having identified the carry-over effects of early exposure reported in the literature, we propose areas that we believe warrant the most urgent attention for further research to better understand the role of developmental plasticity in the responses of marine organisms to global change. Highlights: The potential benefits of plasticity depend on several factors. Further knowledge of concurrent effects of several environmental factors is needed. It is also crucial to pursue and deepen transgenerational work. Models should take phenotypic plasticity into greater account.